A PSYCHOSOMATIC VICIOUS CIRCLE OF MYOCARDIAL INFARCTION - E. О. Taratukhin; I. G. Gordeev; A. Yu. Lebedeva (Российский кардиологический журнал)
The review presents recent studies demonstrating somatic shifts in psychological processes regarded as the risk factors for myocardial infarction: depression, stress, anxiety. Based upon a metaphorical term “a perfect storm”, inflammatory, immunological, neuro-humoral predisposing factors are presented, important for myocardial infarction development, as such shifts themselves, which are the somatic substrate for psychological states mediating myocardial infarction development through behavioral and biological risk factors: “sickness behavior”, “depression illness”. Both directions complete a vicious circle of psychosomatic changes. The emphasis is set on the importance of individual approach to rehabilitation and secondary prevention of myocardial infarction, as, from biopsychosocial point of view, the bottom-up and top-down psychosomatic links are unique for any patient.